Dynamic physical education for secondary school students - Brusseau, Timothy A. Jr.; Darst, Paul W.; Pangrazi, Robert P.; Erwin, Heather 1979- (Champaign, IL Human Kinetics, 2021)
"DPE emphasizes the skill development, activity promotion, and physical fitness behaviors that are the foundation of physical literacy. DPE advocates instructional practices designed to create a learning environment where students are free to experiment, learn, and experience physical activity in a positive climate. DPE goes beyond physical education classes by promoting physical activity throughout the school day and beyond"--
Chapter 1 Physical education in the secondary school -- Chapter 2 Curriculum approaches -- Chapter 3 Steps in developing an effective curriculum -- Chapter 4 Planning for effective instruction -- Chapter 5 Improving instructional effectiveness -- Chapter 6 Teaching styles -- Chapter 7 Management -- Chapter 8 Assessment, evaluation, grading, and program accountability -- Chapter 9 Including students with disabilities -- Chapter 10 Safety and liability -- Chapter 11 Supporting and advocating for physical education -- Chapter 12 Comprehensive school physical activity programs -- Chapter 13 Intramurals, physical activity programs, and athletics -- Chapter 14 Introductory activities -- Chapter 15 Physical fitness -- Chapter 16 Healthy lifestyles -- Chapter 17 Nontraditional activities -- Chapter 18 Sports -- Chapter 19 Lifestyle activities -- Chapter 20 Adventure activities
"This book is a revised edition of Dynamic Physical Education for Secondary School Students, eighth edition, published in 2015 by Pearson Education, Inc" -- T.p. verso.
Includes bibliographical references and index